Teleconsultation in respiratory medicine – A position paper of the Portuguese Pulmonology Society - Morais, A. (2022)
Funding Information: Literature review and medical writing support for this article was provided by Keypoint - Consultoria Científica, Lda., and was funded by Bial. Publisher Copyright: © 2022 Sociedade Portuguesa de Pneumologia